Effect of La on oxidation properties and mechanism of high-speed steel rolls - Si-Min Wang; Hao-Nan Li; Gui-Ying Qiao; Long-Sheng Peng; Yi Wang; Fu-Ren Xiao (Journal of Materials Research and Technology)
The formation mechanism of oxide film on the surface of high-speed steel for rolls was investigated using various characterization methods, and the effect of La modification on the oxidation properties of high-speed steel for rolls was studied. The results showed that differential oxidation occurred in the high-speed steel matrix and eutectic carbide regions, where the MC eutectic region was the first to be oxidized while the M6C region was the last to be oxidized. The matrix oxide film has a three-layer structure: the inner layer of Cr2O3, the middle layer of Fe–Cr spinel oxide, and the outer layer of Fe2O3/Fe3O4. In contrast, the MC eutectic region has an additional layer of FeVO4 in the outermost layer. In addition, the addition of La does not change the type of oxide film formed by isothermal oxidation of high-speed steel. However, the La element improved the size and distribution of MC-type carbides, and these improvements in microstructure make the oxide film more evenly dispersed and ultimately improve the oxidation resistance of HSS used in rolls, where 0.25 wt % of La reduced the weight gain of HSS by 32% when oxidized at 700 °C.